Monensin: an overview of its application in lactating dairy cow diets - DeFrain, J.M.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The efficiency of feedstuff utilization by ruminal microorganisms and the cow’s genetic ability to convert feed nutrients into milk and milk components are major factors that influence the profitability of a dairy herd. Monensin’s ability to modify the movement of ions across biological membranes leads to alterations in bacterial populations and subsequent changes in the proportion of volatile fatty acids produced during ruminal fermentation. Manipulating ruminal microbial populations with ionophores has the potential to improve performance by reducing ketosis, acidosis, and bloat and increasing digestive efficiency. Monensin improves fiber digestion by preventing suboptimal ruminal pH, enhances amino acid use by reducing the degradation of dietary protein, and improves the energy status of periparturient animals. Monensin is not approved for use in diets for lactating dairy cows at this time, but its status is currently under review by the U.S. Food and Drug Administration. If approved, monensin will provide another management tool to the dairy industry.
Keywords: Dairy; Ionophore; Health; Efficiency